Municipal Solid Waste (MSW) recycling behaviour among form three students in Putrajaya (IR) - Nurul Ashikin Izhar (2016)
Students whom are the future leader of the country were assessed to study their behaviour towards Municipal Solid Waste (MSW) recycling. A total of 302 form three students were randomly chosen from nine secondary schools in PutraJaya. An instrument namely Students Behaviour on Recycling (SBoR) that consist of Theory of Planned Behaviour (TPB) (attitude, subjective norm, and perceived behaviour control) and Others Determinant Factors (ODF), (awareness, knowledge of issue, motivation, preferences scheme, recycling practice, and situational factors) were administered to the respondents. The data was analysed using descriptive analysis, Spearman correlation, and standard multiple regression. 77.5% and 22.5% of the students possess excellent and good behaviour towards MSW recycling, respectively. There is weak-positive correlation between TPB and students behaviour with r=0.450 (p=0.000), and strong-positive correlation between ODF and students behaviour with r=0.691 (p=0.000). 20.4% of R2 shows that attitude, subjective norms, and perceived behaviour control of TPB had influence students behaviour with standardised beta weights 0.265, 0.189, and 0.166, respectively. 43.9% of R2 explained that awareness, recycling practice, and situational factors of ODF are the contributor influencer of students MSW recycling behaviour with standardised beta weights 0.341, 0.296, and 0.269, respectively. In conclusion, students have high potential as MSW recycling practitioner and the data obtained also reflects solid waste management measures that shall be strengthen to ensure a sustainable environment in Malaysia.